Correction: Organ-on-a-chip with integrated semitransparent organic electrodes for barrier function monitoring. Issue 7 (7th March 2023) - Marrero, Denise; Guimera, Anton; Maes, Laure; Villa, Rosa; Alvarez, Mar; Illa, Xavi
Abstract : Correction for 'Organ-on-a-chip with integrated semitransparent organic electrodes for barrier function monitoring' by Denise Marrero et al., Lab Chip, 2023, ; https://doi.org/10.1039/d2lc01097f .